2022
DOI: 10.1021/acsomega.2c00316
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Atom-Substituted Quinazoline Derivatives with Faint Emission as Potential Sunscreens

Abstract: Two novel compounds (HQS and HQSe) with excited-state intramolecular proton transfer (ESIPT) properties were designed based on the compound 2-(2-hydroxy-3-ethoxyphenyl)-3 H -quinazolin-4-one (HQ). The parameters related to the ESIPT properties and electronic spectra of HQ and its derivatives were calculated using density functional theory and time-dependent density functional theory methods. The obtained geometric configurations, infrared vibrational spectra, and reduced density gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The hydrogel, ChCrQ, shows stimulating photophysical properties for their significant keto–enol tautomerization involved in CrQ moieties. , This process, known as excited state intramolecular proton transfer (ESIPT), can be influenced by the hydrogel network’s chemical and physical environment due to functional group variations. In water, ChCrQ shows distinct absorption bands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogel, ChCrQ, shows stimulating photophysical properties for their significant keto–enol tautomerization involved in CrQ moieties. , This process, known as excited state intramolecular proton transfer (ESIPT), can be influenced by the hydrogel network’s chemical and physical environment due to functional group variations. In water, ChCrQ shows distinct absorption bands.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the surrounding oxygen atoms are yellow, reflecting a negative potential due to the presence of lone pairs. 1,39 Figure 7c depicts the various intermolecular interactions among ChCrQ molecules. These interactions 52 include the steric effect (red), van der Waals interactions (green), and H-bonding (blue).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]…”
Section: Supporting Informationmentioning
confidence: 99%
“…Song et al [39] reported that the ESIPT process was easy to occur when the PA in its structure has heavier sulfur atom. Zhang et al [40] designed two new ESIPT compounds on the basis of 2‐(2‐hydroxy‐3‐ethoxyphenyl)‐3 H ‐quinazolin‐4‐one (HQ) by S and Se atoms substitution. They found that the S‐substituted and Se‐substituted compounds can absorb UV light strongly.…”
Section: Introductionmentioning
confidence: 99%